Language change and linguistic theory. Volume I, Approaches, methodology, and sound change - Miller, D. Gary. (New York ; Oxford : Oxford University Press, 2011)
This book investigates a large range of changes and their motivations in all parts of the grammar and lexicon. The core argument is that, in the absence of a Grand Unification Theory in linguistics, a natural language changes. Changes occur in successive formal grammars.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed Jan. 10, 2011).
Keywords: Linguistic change